Ghrelin is present in teeth - Aydin, Suleyman; Ozercan, Ibrahim Hanefi; Geckil, Hikmet; Dagli, Ferda; Aydin, Suna; Kumru, Sinem; Ozercan, Mehmet Resat (Springer Singapore Pte Ltd, 2007)
Ghrelin belongs to the family of a gut-brain hormone that promotes food intake and controls energy balance. Recently, it has also been shown to regulate bone formation directly. Dental tissue shares several functional, developmental and anatomical similarities with bone, and in the present study we have investigated the presence of ghrelin in 44 human teeth using immunocytochemistry and radioimmunoassay. Both methods showed that the hormone is present in canines and molars, mainly in the odontoblasts but also in the pulp. Ghrelin could potentially play interesting physiological roles in teeth.
Keywords: ghrelin; odontogenic cell; peptide hormones; tooth